Recognizing the stranger : recognition scenes in the Gospel of John - Larsen, Kasper Bro. (Biblical interpretation series,, 2008)
Recognizing the Stranger is the first monographic study of recognition scenes and motifs in the Gospel of John. The recognition type-scene ( anagnōrisis ) was a common feature in ancient drama and narrative, highly valued by Aristotle as a touching moment of truth, e.g., in Oedipus' tragic self-discovery and Odysseus' happy homecoming. The book offers a reconstruction of the conventions of the genre and argues that it is one of the most recurrent and significant literary forms in the Gospel. When portraying Jesus as the divine stranger from heaven, the Gospel employs and transforms the formal and ideological structures of the type-scene in order to show how Jesus' true identity can be recognized behind the half-mask of his human appearance.